The Analysis of Input Optimization for Cassava (Manihot esculenta) Production in the Marga Tiga Sub-District East Lampung District - Feby Musti Ariska; Ainul Mardliyah; Sri Puji Lestari; Yuni Elmita Sari (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
This study aims to ascertain how production inputs affect cassava farming production and examine how to use production inputs as efficiently as possible. The research location was selected because the research area is a center for cassava production. The Cobb-Douglas production function model is an analytical technique used to assess how production inputs affect cassava output. Analyze the level of input utilization optimization at the same time by comparing the marginal product's value to other inputs. The study's variables included land area, labor, seeds, urea-fertilizer, NPK-fertilizer, ZA-fertilizer, SP36-fertilizer, herbicides, and production yields. The result of this research is that production inputs simultaneously influence cassava production. Several production inputs used in cassava farming in Marga Tiga District are still not optimal and need to be added, including land area, organic fertilizer, urea fertilizer, and ZA fertilizer. Meanwhile, several other production inputs, namely labor, seeds, NPK fertilizer, SP 36 fertilizer, and herbicides, are not optimal, so farmers need to reduce them.